Clinical relevance of circulating autoantibodies in idiopathic pulmonary fibrosis; A NAt hard to break - Kirgou, Paraskevi; Sinis, Sotirios I.; Dimeas, Ilias E.; Papanikolaou, Ilias C.; Tatsis, Konstantinos; Gogali, Athena; Gourgoulianis, Konstantinos I.; Bogdanos, Dimitrios P.; Daniil, Zoe (Frontiers in Medicine, 2022)
Patients with idiopathic pulmonary fibrosis patients are screened for circulating autoantibodies as part of the initial interstitial lung disease workup. Management of seropositive idiopathic pulmonary fibrosis is currently considered no different than that of lone idiopathic pulmonary fibrosis. Emerging data however suggest that they may possess distinct characteristics in terms of pathophysiology, histopathology, prognosis and amenability to immunomodulation. In that context, the aim of our study was to evaluate the influence of autoantibody status on: i) the decline of forced vital capacity; ii) the decline of diffusing capacity of lung for carbon monoxide; and iii) 3-year survival; in a cohort of 102 idiopathic pulmonary fibrosis patients. In a pilot sub-study, we also sought to evaluate whether changes in antibody status during disease course affect the aforementioned parameters by potentially reflecting activity of the autoimmunity component of the pro-fibrotic mechanism.